Seasonal Aspects of the Diet of the Volga Population of the Eastern Imperial Eagle During the Breeding Season - Mikhail V. Korepov (Пернатые хищники и их охрана)
Diet is a key factor in determining the status of large raptor populations. Regional studies of the diet of the Volga population of the Eastern Imperial Eagle (Aquila heliaca) are mainly based on the collection of food remains and scats at nesting sites. This method allows a rather complete identification of prey species composition and in some cases their quantitative ratio, but seasonal aspects of prey spectra remain poorly studied. Observations were made at an Imperial Eagle nest in the Cherdaklinsky district, Ulyanovsk Region (Zavolzhye), during three breeding seasons (2019–2021) from March to September.